Transposable element expression and sub-cellular dynamics during hPSC differentiation to endoderm, mesoderm, and ectoderm lineages - Babarinde, Isaac A.; Fu, Xiuling; Ma, Gang; Li, Yuhao; Liang, Zhangting; Xu, Jianfei; Xiao, Zhen; Qiao, Yu; Lin, Zheng; Oleynikova, Katerina; Akinwole, Mobolaji T.; Zhou, Xuemeng; et al. (Nature communications, 2025)
Transposable elements (TEs) are genomic elements present in multiple copies in mammalian genomes. TEs were thought to have little functional relevance but recent studies report roles in biological processes, including embryonic development. To investigate the expression dynamics of TEs during human early development, we generated long-read sequence data from human pluripotent stem cells (hPSCs) in vitro differentiated to endoderm, mesoderm, and ectoderm lineages to construct lineage-specific transcriptome assemblies and accurately place TE sequences. Our analysis reveals that specific TE superfamilies exhibit distinct expression patterns. Notably, we observed TE switching, where the same family of TE is expressed in multiple cell types, but originates from different transcripts. Interestingly, TE-containing transcripts exhibit distinct levels of transcript stability and subcellular localization. Moreover, TE-containing transcripts increasingly associate with chromatin in germ layer cells compared to hPSCs. This study suggests that TEs contribute to human embryonic development through dynamic chromatin interactions. Transposable elements are genetic parasites that have colonised genomes and they express as parts of coding and noncoding RNAs. Here, the authors explore how they are expressed in transcripts in normal human development, and how they alter transcript dynamics.